Can molecular DNA‐based techniques unravel the truth about diabetic foot infections?. Issue 1 (5th July 2016) - Malone, M.; Gosbell, I. B.; Dickson, H. G.; Vickery, K.; Espedido, B. A.; Jensen, S. O.
Summary: Diabetes foot infections are a common condition and a major causal pathway to lower extremity amputation. Identification of causative pathogens is vital in directing antimicrobial therapy. Historically, clinicians have relied upon culture‐dependent techniques that are now acknowledged as both being selective for microorganisms that thrive under the physiological and nutritional constraints of the microbiology laboratory and that grossly underestimate the microbial diversity of a sample. The amplification and sequence analysis of the 16S rRNA gene has revealed a diversity of microorganisms in diabetes foot infections, extending the view of the diabetic foot microbiome. The interpretation of these findings and their relevance to clinical care remains largely unexplored. The advent of molecular methods that are culture‐independent and employ massively parallel DNA sequencing technology represents a potential 'game changer'. Metagenomics and its shotgun approach to surveying all DNA within a sample (whole genome sequencing) affords the possibility to characterize not only the microbial diversity within a diabetes foot infection (i.e. 'which microorganisms are present') but the biological functions of the community such as virulence and pathogenicity (i.e. 'what are the microorganisms capable of doing'), moving the focus from single species as pathogens to groups of species. This review will examine the new molecular techniques for exploration of the microbiome of infected and uninfected diabetic foot ulcers, exploring the potential of these new technologies and postulating how they could translate to improved clinical care. Copyright © 2016 John Wiley & Sons, Ltd.